Gold recovery from flotation concentrate from gold mine tailings using dissolve smelting - Erdenebold U.; Sung C.-M.; Wang J.-P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Gold flotation concentrate may contain relatively high concentrations of valuable metals such as iron, copper, and zinc, and occasionally, even precious metals such as gold. The major components of the concentrate are SiO2, Fe2O3, and Al2O3, but it also contains reactive sulphide minerals such as pyrite. The sulphides in the flotation concentrate are fully converted into an oxide form during oxidative roasting, therefore, the chemical composition of the roasted concentrate is considered to be a copper slag. High temperature smelting with additives to dissolve Au from the gold concentrate into a molten copper was used in the research. Gold greatly dissolved at 1600°С under a CaO/SiO2 ratio of 1.25, suggesting the increase in the dissolution of gold into molten copper with decreasing viscosity of the molten slag-like concentrate at high temperatures.